The Clinical Value of Artery Umbilical Cord Blood Gas in Predicting Neonate Condition: A Prospective Cohort Study - Xing Xin; Weixin Lu; Chunhua Ye; Hongyan Du; Shaoshuai Wang; Ling Feng; Dandan Shi (Wolters Kluwer Health, 2021)
Abstract. Objective:. To evaluate the predictive ability of neonate condition through the traditional parameters and artery umbilical cord blood gas (aUCBG). Methods:. A prospective cohort study was conducted in obstetrics and gynecology department between October 2017 and August 2018 at Tongji Hospital in Wuhan, China, and 360 aUCBG samples were collected. The average age of pregnant women was (29.50 ± 4.42) years, range from 19 to 48 years old. The gestational age range from 28+4 weeks to 41+3 weeks at admission. Logistic regression and area under the curve (AUC) from Receiver operating characteristic curves were used to identify risk factors, such as, premature rupture of membranes (PROM), high blood pressure, premature delivery (PD), low 1-minute Apgar scores (Apgar 1), low 5-minute Apgar scores (Apgar 5), pH, base excess, bicarbonate, neonatal blood sugar (NBS), and so on, to predict neonatal condition and evaluate the predictive ability of traditional and aUCBG parameters. Results:. In all cases, PROM, PD, Apgar 1, Apgar 5, pH, base excess, bicarbonate, total carbon dioxide, and neonatal blood sugar were risk factors and were associated with poor condition of neonate. Apgar 1 were an independent risk factor. Combined traditional and aUCBG parameters had higher AUC of 0.895 (95% confidence interval (CI): 0.830-0.960, P < 0.001). In cesarean section subgroup, high blood pressure, PD, and Apgar 1 were risk factors and were associated with poor condition of neonate. Apgar 1 and low pH were the independent risk factors. Combined traditional and aUCBG parameters had highest AUC of 0.940 (95% CI: 0.886-0.993, P < 0.001). In vaginal delivery subgroup, maternal age above 35 years, PROM, PD, Apgar 1, Apgar 5, and male newborn were risk factors and were associated with poor condition of neonate. Maternal age above 35 years was an independent risk factor. Combined traditional and aUCBG parameters had highest AUC of 0.897 (95% CI: 0.828-0.965, P < 0.001). For pregnant women without comorbidities and complications of pregnancy, aUCBG may not be necessary. Conclusion:. In high-risk pregnancies, especially lower Apgar scores, PD, and maternal age above 35-year old, aUCBG is recommended. Traditional parameters combined with aUCBG might increase the predicting ability of neonate condition.